"Tudni szeretnénk, milyen édesek a tuszi nők": A ruandai genocídiumot megelőző médiadiskurzus szerepe a népirtó nemi erőszakban - Lator, Anna Luca (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
The article presents the characteristics of sexual violence during the Rwandan Genocide at the beginning of the 1990s. Towards the explanation of the phenomenon of conflict related sexual violence, it introduces the milestones of the history of the country and the xenophobic narratives which had led to genocide. Then, with the main focus on media, it analyzes survivors’ testimonies and media materials, to demonstrate how the narratives appeared during the perpetration of rape. The aim of the research is to reveal the power of media with highlighting how political narratives influenced the characteritics of sexual violence.